“Coalition of October 15” vs. “Coalition of December 13”. Colonisation of Time From a Linguistic Perspective - Joanna Szadura, (Respectus Philologicus, 2025)
The subject of the study is the problem of one of the manifestations of human control over time, colonisation. It has two dimensions: the first is colonisation using time, a manifestation of which is creating a common space for establishing temporal interactions (e.g., globalisation of clock time), the second is colonisation of time understood as social interference in time (individual and communitarian). Time colonisation is, among other things, a tool for the struggle for power by imposing a specific valuation on temporal units important for a particular community. The issue of linguistic actions aimed at colonising the past, present, and future by contemporary Polish politicians is the subject of the analysis undertaken. An example subject to observation is the use of two names of the governing coalition after the elections to the Sejm and Senate of the Republic of Poland held on October 15, 2023 (i.e. Coalition of October 15 and Coalition of December 13).
Keywords: time as a linguistic and cultural category; colonization of time; Coalition of October 15; Coalition of December 13